The Effect of Zakat Distribution on Income Inequality The Case in Indonesia - sejati, kharisma rindang (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
Zakat is one of the Islamic economic instruments which is an alternative policy used to reduce income inequality. With the distribution of zakat that is right on target, it can expand the income distribution of weak communities so that benefit and charity can be created. This research aims to determine the effect of zakat on income inequality in Indonesia for the 2016-2022 period, which includes semi-annual Gini ratio index data as a measurement of income inequality, as well as data on annual zakat distribution for 2016-2022 which has been interpolated into semi-annual data. The method used is a simple regression method using secondary data obtained through the BPS Indonesia and BAZNAS Republic of Indonesia websites. The results of the research conducted show that zakat has a significant negative effect on inequality, meaning that the higher the distribution of zakat will reduce income inequality in Indonesia with a significance value of 0.0030. and obtained an R-square result of 0.533, meaning that the zakat variable can explain income inequality by 53.3%